RESOURCE ALLOCATION AND STRATEGY IMPLEMENTATION IN COMMERCIAL BANKS BRANCHES IN MACHAKOS SUB COUNTY - Masya, Mercy; Wamitu, Susan; Weru, Jane (European Journal of Business and Strategic Management, 2022)
Purpose: The implementation of strategies in Commercial Banks in Kenya has been experiencing numerous challenges and only 37% of the strategies are considered to be successfully implemented. Internal constraints during strategy implementation include poor resource allocation. The objective of this study was to establish the effect of resource allocation on strategy implementation in Commercial Banks Branches in Machakos Sub County. Methodology: Descriptive research design was used in this study. The target population of the study was 253 staff working in the top level management, middle level management and low level management in the fourteen Commercial Banks based in Machakos Sub County. Since the population of the top level management in the 14 branches is small, a census was utilized. The study adopted stratified and simple random sampling techniques in the selection of 30 per cent of staff in middle level management and low level management of each bank. The study utilized primary data, which was collected by use of questionnaires. Descriptive and inferential statistics were used in analysing the quantitative data with the help of the Statistical Package for the Social Sciences (SPSS version 24) statistical software. Descriptive statistics included frequencies, percentages, mean, and standard deviation. Inferential statistics included correlation and regression analysis. The results were presented in pie charts and tables. Findings: The study found that resource allocation has a significant effect on strategy implementation in Commercial Banks Branches in Machakos Sub County Unique Contribution to Theory, Practice and Policy: The findings of this study support the Resource Based View Theory which argues that strategic resources have the potential to deliver comparative advantage to a firm. As a regulator, the Central Bank of Kenya (CBK) should come up with policies to guide the allocation and utilization of resources during strategy implementation so as to protect investors in the commercial banks in Kenya. The study recommends that the management of Commercial Banks' Branches in Machakos Sub County should ensure timely and adequate allocation of resources in order to ensure that the set objectives are achieved within the set budget during strategy implementation.